A characterization of the English spoken by tertiary English and Mathematics teachers in selected universities in Metro Manila - Aranas, Patria Garcia (Education quarterly.)
This study attempted to describe the Philippine variety of English as spoken by teachers of college freshman English and mathematics in selected universities in Metro Manila for the purpose of establishing the forms of the Philippine Variety of English spoken by educated speakers. Features of the Philippine Variety of English were based on the categories defined by Sridhar which included lexical and syntactic forms.